A Study on Barn Owl Population (Tyto alba var. javanica) in Reducing Rat Attacks and Parthenocarpy in Oil Palm Fresh Fruit Bunches - Budihardjo, Kadarwati; Wirianata, Herry; Primananda, Septa (Bioma : Berkala Ilmiah Biologi, 2019)
In mature oil palms, rat attacks fruit bunches, causing significantly reduction in the potential yield and the quality of oil palm fruit bunches. Rat is also known to consume the post anthesis male flowers which act as the breeding sites for the eggs and larvae of Elaeidobius kamerunicus pollinator beetle. Indirectly, the pollinator beetle population can be reduced in high rat infestation area, affecting the pollination and increasing the percentage of parthenocarpic fruit bunches. The barn owl (Tyto alba var. javanica) is a rat biological control agent in the oil palm plantations. The study conducted at PT. Mustika Sembuluh in Central Borneo shows that barn owl (T. alba) population is significantly correlated with both rat attacks and parthenocarpic percentage of oil palm fruit bunches in oil palm plantation